1996
DOI: 10.1063/1.361864
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bias enhanced nucleation of diamond on silicon

Abstract: The process of bias enhanced nucleation of microwave chemical vapor deposited diamond on silicon has been extensively characterized using plasma diagnostics, scanning and transmission electron microscopy (TEM), Raman spectroscopy, and x-ray diffraction. The nucleation kinetics were measured as a function of bias voltage, methane partial pressure, and substrate temperature. The nucleation is found to be transient in character, with a delay time followed by an exponential increase in nucleation density with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…BEN nucleation requires an incubation time as previously reported by Stoner et al 3 and Gerber et al 18 The nucleation incubation time, in our experiments, was found to vary across each sample. In the central region, assigned A, some small islands were formed after 5 min bias enhanced nucleation, as shown in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…BEN nucleation requires an incubation time as previously reported by Stoner et al 3 and Gerber et al 18 The nucleation incubation time, in our experiments, was found to vary across each sample. In the central region, assigned A, some small islands were formed after 5 min bias enhanced nucleation, as shown in Fig.…”
Section: Resultssupporting
confidence: 86%
“…The corresponding bias voltage and duration are also listed. Oriented region ͑mm from the center͒ 10-35 14-32 15-30[15][16][17][18][19][20][21][22][23][24][25] …”
mentioning
confidence: 99%
“…2,6 The film adhesion, surface roughness, and growth rate of UNCD films are controlled by nucleation and growth processes. [6][7][8] The biasenhanced nucleation ͑BEN͒ process investigated by several groups has several advantages over mechanical polishing or ultrasonic seeding processes, namely, ͑a͒ better efficiency, 9 ͑b͒ stronger adhesion to substrates, [8][9][10][11] and ͑c͒ an integrated fully dry nucleation/growth process using plasma processing only. Prior work 8 demonstrated that the BEN process enhances UNCD film adhesion to substrates, although UNCD films were grown using an Ar/ CH 4 chemistry without bias, on BEN layers produced by 70 mbar H 2 / CH 4 plasma chemistry.…”
mentioning
confidence: 99%
“…Experimental methods for diamond nucleation on nondiamond substrates (the first necessary step of a heteroepitaxial growth process) have also been developed (4-7). The most effective method uses bias-enhanced nucleation (BEN) (4,(6)(7)(8)(9)(10), in which the target is biased, with a relatively methanerich CH 4 /H 2 mixture (several percent methane) as a first step, followed by a conventional CVD step (typically 1% methane or less). However, the nucleation mechanism of diamond on nondiamond substrates remains poorly understood (11), largely because of the tremendous difficulty of locating and identifying the nucleation sites.…”
mentioning
confidence: 99%